Ecological Niche Changes and Risk Regionalization of the Invasive Plant Praxelis clematidea - Jia‐Guo Wang; Jia‐Wei Wu; Wei‐Jie Li (Ecology and Evolution, 2025)
ABSTRACT Praxelis clematidea is a noxious invasive weed. Understanding the dispersion trends and niche changes inherent to P. clematidea will be helpful for monitoring this invasive species and for providing early warnings of its spread and developing appropriate scientific prevention and control measures. In this study, the invasion risk zones of P. clematidea in Guizhou Province were classified via MaxEnt, Zonation, and ArcGIS. The dispersion trend was predicted, and the ecological niche change was quantified via the R software ecospat package. The results revealed that (1) the current high‐risk areas for P. clematidea invasion in Guizhou cover 14,096.03 km2, concentrated mainly in the western to southern regions (Liupanshui, Anshun, Qianxinan, and Qiannan); the medium‐risk areas cover 21,144.04 km2, concentrated mainly in the southwestern region (Anshun, Qiannan); and the low‐risk areas cover 26430.05 km2, occurring in all cities of Guizhou but concentrated mainly in the small areas outside the high‐ and medium‐risk areas. (2) From the present until the 2050s, the risk areas of P. clematidea will expand mainly toward the southeastern parts; from the 2050s to the 2070s, the risk areas will decrease in the southeast; and from the 2070s to the 2090s, they will expand at a large scale in the central and northeastern parts. Overall, the trend is toward expansion. (3) The degree of ecological niche overlap between P. clematidea in Guizhou Province and its original habitat is very low (Schoener's D= 0.12); the rates of niche expansion, stability, and underfilling are 0.88, 0.12, and 0.96, respectively, indicating niche instability. P. clematidea invades and occupies areas with relatively high precipitation during the warmest season in Guizhou Province. Compared with the temperature preferences in the coldest season in the original area, this species can adapt to low temperatures.